Kajian Hak Milik Tanah Bandar - Urban Land Ownership Study : Urban Expansion And Land Ownership In The Rural-urban Fringe - Dieter, Hans (USM, 1975)
There has certainly been no lack of studies on urbanization and urban life from the turn of the century. Many aspects have been discussed and considerable progress has been made in understanding the process of urbanization and the change of urban social structure over time.